Assistance in Capacity Building for the PKK Group in Mekarsaluyu Village, Bandung Regency Through the Implementation of SDGs Programs for Stunting Prevention - Ratna Poerwantika, Tine; Windary, Shylvia; Aini Farhati, Inggit (Jurnal Pengabdian Masyarakat Formosa, 2024)
Community Service (PKM) was conducted in collaboration with the PKK cadres of Mekarsaluyu Village. Mekarsaluyu Village is located in Bandung Regency, directly bordering Bandung City. Several stunting cases are still occurring in this village. The Family Welfare Empowerment Group (PKK) is directly involved in addressing stunting, with programs aimed at facilitating the community's access to healthcare services. The proposed solutions are as follows: 1) Providing further understanding of the SDGs program, 2) Offering counseling on the prevention and management of stunting cases to PKK members, 3) Socializing SDGs programs that can be implemented by PKK members. The methods used to achieve the target solutions include Counseling, Coaching, and Facility Assistance.